Порівняльна характеристика природних та інтродукційних популяцій Adonis vernalis L. - Parubok, M.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The results of comparative study of populations of Adonis vernalis L. (Ranunculaceae) in natural habitats and artificial steppe phytocenoses of Ukraine are presented. The main parameters of natural and introduced populations have been characterized. Modeling of the populations of rare plant species in artificial steppe ecosystems have been considered as a method of their ex situ protection.